2000
DOI: 10.1089/15270290050074251
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Anesthesia at High Altitude

Abstract: There is a clinical need for a safe and effective anesthetic technique in high altitude and remote areas. This report presents a series of 11 consecutive cases documenting the use of ketamine anesthesia in a remote hospital at an altitude of 3,900 m, by primary-care physicians without specialist training in anesthesia. The method of administration is fully described. At a low dose of 2.0 mg/kg, ketamine produces a dissociative anesthesia that does not depress the hypoxic drive, or interfere with the pharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Bishop et al reported a case series of 11 haemodynamically stable patients undergoing urgent surgery for trauma or local sepsis at Khunde Hospital, Nepal (3900 m above sea-level) [8]. Anaesthesia was administered by primary care physicians with no specialist training in anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bishop et al reported a case series of 11 haemodynamically stable patients undergoing urgent surgery for trauma or local sepsis at Khunde Hospital, Nepal (3900 m above sea-level) [8]. Anaesthesia was administered by primary care physicians with no specialist training in anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of ketamine anaesthesia at high (1500-3500 m above sea-level) or very high altitude (3500-5500 m above sea-level) [1] have involved elective or urgent cases who were haemodynamically stable [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Lowdose ketamine resulted in sustained apnea, possibly by central medullary chemoreceptor impairment, in one report [92]. Conversely, one small study of 11 patients at 3840 m found that low-dose ketamine (∼2.0 mg·kg −1 ) with midazolam produced dissociative anesthesia that did not depress the hypoxic respiratory drive significantly, nor did it interfere with the pharyngeal or laryngeal refl exes [93]. Supplemental O 2 had to be administered to 3 of these 11 patients when the O 2 saturation fell below 80% and was not corrected by a jaw thrust or stimulation [93].…”
Section: Anesthesia Management At Hamentioning
confidence: 97%
“…Conversely, one small study of 11 patients at 3840 m found that low-dose ketamine (∼2.0 mg·kg −1 ) with midazolam produced dissociative anesthesia that did not depress the hypoxic respiratory drive significantly, nor did it interfere with the pharyngeal or laryngeal refl exes [93]. Supplemental O 2 had to be administered to 3 of these 11 patients when the O 2 saturation fell below 80% and was not corrected by a jaw thrust or stimulation [93]. Maharjan [94] suggest that ketamine anesthesia for cleft lip repair is practical and costeffective in remote areas in Nepal.…”
Section: Anesthesia Management At Hamentioning
confidence: 98%
See 1 more Smart Citation